Adoption of integrated crop-livestock management practices (ICLMPs) among men and women smallholder farmers in Ghana. (4th May 2021) - Asante, Bright Owusu; Koomson, Isaac; Villano, Renato A.; Wiredu, Alexander Nimo
Abstract: Integrated crop-livestock management practices (ICLMPs) play a vital role in ensuring food security and improved welfare for smallholder households, however, studies that focus on ICLMP adoption in Ghana (including its gender dimension) remain scant. This paper examines gender differences in the drivers and intensity of ICLMP adoption using farm-level data from 638 smallholder farmers in Ghana. Employing Multivariate Probit, Tobit regression models and dominance analytical procedures, we find that adoption of ICLMPs is generally influenced by non-farm income, extension contacts and nativity. While age, credit access, soil fertility, distance to markets, total value of assets and research contacts influence the intensity of ICLMP adoption among the men, intensity of adoption among women farmers is influenced mainly by household size. The dominance analysis showed that being a native of the community/village where one farms had the strongest influence in intensifying ICLMP adoption, with gender differences being evident regarding the relative influence of the other variables. Policies to enhance the adoption of ICLMPs in Ghana could be designed to focus on women farmers who have large farm assets, access to extension and are engaged in non-farm income-generating activities